2013
DOI: 10.4236/eng.2013.510098
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Rooftop Rainwater Harvest Potential: Case of Mbeya University of Science and Technology in Mbeya Tanzania

Abstract: The advantages that the rooftop rainwater harvesting system has as a source of water supply have been examined. The observed daily rainfall records of 10 years and the current total roof area of the facilities at Mbeya University of Science and Technology as the catchment area were used. Using a water balance model to determine the suitable water use that will cover 100% of the time, the model indicated that for the current roof area a water supply of 120 lts per day can be met when a storage tank whose capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Several researchers have developed/applied models for optimizing tank size and assessing storage tank performance (Ndomba & Wambura 2010;Campisano & Modica 2012;Imteaz et al 2012;Mun & Han 2012;Katambara 2013). Most such analyses consider fixed demand through the year, regardless of the variable nature of rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have developed/applied models for optimizing tank size and assessing storage tank performance (Ndomba & Wambura 2010;Campisano & Modica 2012;Imteaz et al 2012;Mun & Han 2012;Katambara 2013). Most such analyses consider fixed demand through the year, regardless of the variable nature of rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Rainwater is considered a viable alternative where water is saline, as in the case of the study area. Scholars have, however, found that the practice of rainwater harvesting is still low in Tanzania (Katambara, 2013; Mwamila, Han, & Katambara, 2016; Umeodum et al, 2019).…”
Section: Resultsmentioning
confidence: 99%